Perinatal exposure to earthquake stress increases the risks of hypertension and diabetes in subsequent adult life: A cross‐sectional study. Issue 12 (30th October 2020) - Li, Na; Yu, Lu‐Lu; Zhao, Xiao‐Chuan; Song, Mei; Wang, Lan; Gao, Yuan‐Yuan; Lu, Wen‐Ting; Wang, Xue‐Yi; Wang, Yu‐Mei
Abstract: The objective of the current study was to determine whether exposure to earthquake stress during pregnancy and infancy impacted on the risk of chronic adult health problems. All subjects were divided into three groups: the infant exposure group, the fetus exposure group, and the non‐exposure group. All subjects completed a standardized interview that included questions on demographic information, traumatic experiences during the earthquake, Anthropomorphic parameters such as body height, weight, and blood pressure were measured. Traumatic events in childhood and adulthood were assessed by the Childhood Trauma Questionnaire (CTQ) and Life Event Scale (LES), respectively. Totally1325 subjects were included; 399 subjects experienced the earthquake as fetuses, 374 subjects who experienced the earthquake as infants and 552 subjects did not experience the earthquake. The three groups were comparable in sociodemographic and baseline characteristics except age (Infant exposure vs Prenatal exposure vs No exposure = 39.5 ± 0.6 vs 38.5 ± 0.8 vs 37.5 ± 0.9, p < .001). Fetal and infant exposure to earthquakes was associated with elevated systolic blood pressure (both were + 3 mm Hg, p < .001). After adjustment for covariates, earthquake exposure in infants (odds ratio [OR] = 2.010, 95% confidence interval [CI] = 1.216 3.322) and fetuses (OR = 1.509, 95% CI = 1.014 2.248) was a significant and independent risk factor for hypertension. Earthquake expose in fetuses was a significant and independent risk factor for diabetes (OR = 2.307, 95% CI = 1.136 4.686). Earthquake exposure in infants and fetuses is a significant and independent risk factor for hypertension. Earthquake exposure in fetuses is significant and independent risk factor for diabetes.